Neoliberalism in the South African post-apartheid regime: economic policy positions and globalisation impact - Sebake, B. K. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The period of more than two decades of democracy, South African government has trampled into a policy revamp as a mechanism of crafting and crystalising new order of public administration in the new regime. It is envisaged that any society emerged out of liberation struggle may trample after one to two decade/s in power, which this view become relevant to access the performance of democracy in South Africa in relation to the policy perspective, economic impact in the context of globalisation. It is arguable that post 1994, government of the African National Congress (ANC) had establish its policy positions on neoliberalism, which create an opportunity to make a deep analysis through the scholarship of public administration. The paper is a conceptual analysis of the literature and empirical evidence on governance praxis, political ideology influence in the manner in which the post-apartheid government in South Africa have succeeded, failed and work in progress. The paper provides a historic reflection of neoliberalism in the context of New Public Management (NPM), policy direction of the post-apartheid, trade controls against the mineral resources, private sector influence on public sector, capacity of private sector and its impact on public service, fiscal position and economic growth etc. These concepts are engaged in the context of assessing the state and impact on the current era on maturing democracy. The methodology will summarily be some mixed methods inter alia: – qualitative and quantitative is used as a secondary data to often illustrate the impact on the focus areas. The paper is then concluded and recommendations of a scientific oriented solution in relation to topical strategic focus areas of the paper are provided.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Neoliberalism; New public management; Policy perspective; Democracy; Political ideology; Economic perspective; Neoliberalism; Post-apartheid era -- South Africa